Application of Organic Fertilizers Affect the Citrus Leafminer, Phyllocnistis citrella (Lepidoptera: Gracillariidae) Infestation and Citrus Canker Disease in Nursery Plantations. (June 2019) - Ullah, Muhammad Irfan; Riaz, Muhammad; Arshad, Muhammad; Khan, Aqeel Haider; Afzal, Muhammad; Khalid, Samina; Mehmood, Naunain; Ali, Sajjad; Khan, Arif Muhammad; Zahid, Syed Muhammad Ali; Riaz, Maryam
Citrus leafminer (CLM), Phyllocnistis citrella Stainton (Lepidoptera: Gracillariidae), is one of the most important insect pests of Pakistan's citrus nursery stock and caused extensive damage to young flushes. The organic compost is a widespread technique used to manage insect pests and plant diseases. Different composts (biofert, tara root and vermicompost) at 0.5 and 0.25 kg/plant concentration in comparison to NPK fertilizer at 0.4 and 0.2 g/plant were evaluated for CLM infestation and the associated citrus canker disease in nursery plantations of Citrus reticulata Blanco. Application of biofert at 0.5 kg/plant reduced the CLM infestation up to 54.5% during Fall-2016 and 39.1% during Summer-2017 in comparison to control treatment. The CLM larval density was also found lower by the application of biofert followed by vermicompost during both seasons. Both concentrations of biofert followed by vermicompost at 0.5 kg/plant resulted in remarkable protection against citrus canker disease in both flushes. The incidence of canker associated with CLM infested leaves was also studied and found lower by the application of biofert and vermicompost compared with control treatment. Conclusively, the soil amendment using biofert and vermicompost affects the CLM population and canker infection in nursery plantations. These organic fertilizers can be used in future citrus IPM programs as a tool to suppress the CLM population and citrus canker disease.